2010
DOI: 10.1364/boe.1.001432
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of biological chromophores using diffuse optical spectroscopy: benefit of extending the UV-VIS wavelength range to include 1000 to 1600 nm

Abstract: With an optical fiber probe, we acquired spectra from swine tissue between 500 and 1600 nm by combining a silicon and an InGaAs spectrometer. The concentrations of the biological chromophores were estimated by fitting a mathematical model derived from diffusion theory. The advantage of our technique relative to those presented in previous studies is that we extended the commonly-used wavelength ranges of 500 and 1000 nm to include the range of 1000 to 1600 nm, where additional water and lipid absorption featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
180
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(184 citation statements)
references
References 29 publications
(51 reference statements)
4
180
0
Order By: Relevance
“…These observations originate from different chromophores for both primary and secondary tumor types. Since metastases consist of abnormal cells with their origin in other organs, the amount of bile with high absorption between 400 nm and 500 nm is low [17,18,31]. Extracted from diffuse reflectance spectra, Nachabé et al [18] have shown that the amount of bile in metastatic tumor tissues is 80% lower than in healthy liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These observations originate from different chromophores for both primary and secondary tumor types. Since metastases consist of abnormal cells with their origin in other organs, the amount of bile with high absorption between 400 nm and 500 nm is low [17,18,31]. Extracted from diffuse reflectance spectra, Nachabé et al [18] have shown that the amount of bile in metastatic tumor tissues is 80% lower than in healthy liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of our technique relative to those presented in most previous studies is that the narrow wavelength range commonly used in DRS (typically between 400 and 900 nm) was extended into the near-infrared region up to 1,600 nm (21,22), where blood has no significant absorption features. The main benefit of this feature is that it helps to overcome the effect of dominant absorption by excessive amounts of hemoglobin in the visible wavelength region (400-700 nm; ref.…”
Section: Portable Spectroscopy Systemmentioning
confidence: 99%
“…The main benefit of this feature is that it helps to overcome the effect of dominant absorption by excessive amounts of hemoglobin in the visible wavelength region (400-700 nm; ref. 22). …”
Section: Portable Spectroscopy Systemmentioning
confidence: 99%
“…This recipe was designed to produce phantoms of optical properties mimicking those of human skin which had high absorption at 600 nm (due to hemoglobin and melanin absorption) and low scattering at 1200 nm (as those indicated in refs [15]. and [21]). The two phantoms, LP_a and LP_b, were controlled to have a same μ s '/μ a value.…”
Section: Liquid Phantommentioning
confidence: 99%
“…This suggests that the validity of SDE becomes more tenuous as the wavelength increases above 1000 nm. Several groups have used different approaches to investigate the in-vivo skin optical property spectra in the wavelength range from 1000 to 1350 nm [16][17][18][19], and this wavelength region has been demonstrated to be a crucial region for accurate recovery of the water and lipid concentrations of biological tissues in the studies employing broad wavelength continuous wave light sources [20,21]. The LGLSI measurement geometry allows the use of the δ-P 1 diffusion model based spectral analysis on the measured diffuse reflectance so that the broadband optical property spectra of samples can be accurately derived within one second even at wavelengths where sample μ s '/μ a is close to unity.…”
Section: Introductionmentioning
confidence: 99%